Liquidity matters: evidence from the Russian interbank market - Alexei Karas; Koen Schoors; Gleb Lanine (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
We suggest an additional transmission channel of contagion on the interbank market - the liquidity channel. Examining the Russian banking sector, we and that the liquidity channel contributes significantly to understanding and predicting interbank market crises. Interbank market stability Granger causes the interbank market structure, while the opposite causality is rejected. This bolsters the view that the interbank market structure is endogenous. The results corroborate the thesis that prudential regulation at the individual bank level is insufficient to prevent systemic crises. We demonstrate that liquidity injections of a classical lender of last resort can effectively mitigate coordination failures on the interbank market both in theory and practice. Apparently, liquidity does matter.
URN:NBN:fi:bof-201408072099
Keywords: 330